2020
DOI: 10.3389/fnhum.2020.00243
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Brain Functional Connectivity and Efficiency During an Endurance Cycling Task: A Source-Level EEG and Graph Theory Approach

Abstract: Various methods have been employed to investigate different aspects of brain activity modulation related to the performance of a cycling task. In our study, we examined how functional connectivity and brain network efficiency varied during an endurance cycling task. For this purpose, we reconstructed EEG signals at source level: we computed current densities in 28 anatomical regions of interest (ROIs) through the eLORETA algorithm, and then we calculated the lagged coherence of the 28 current density signals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…A bilateral connectivity pattern of information flow during different exertion levels was observed by Comani et al [271]. A recent study addressed the functional brain patterns and network topology during a cycling task [281]. Three graph theory measures were computed in EEG source level for six different difficulties.…”
Section: E Connectivity Studies Of Physical Exertionmentioning
confidence: 89%
“…A bilateral connectivity pattern of information flow during different exertion levels was observed by Comani et al [271]. A recent study addressed the functional brain patterns and network topology during a cycling task [281]. Three graph theory measures were computed in EEG source level for six different difficulties.…”
Section: E Connectivity Studies Of Physical Exertionmentioning
confidence: 89%
“…However, there are a few investigations that explore dynamic network properties during a task phase. Tamburro et al explored connectivity and efficiency of the brain networks during an endurance cycling task (Tamburro et al, 2020 ). The study discussed several aspects of global network parameters that could affect behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed Eloc and Cp increase during our decision phase with respect to the rest phase, indicating the transition from the resting state. Moreover, it was suggested that the reduction of global efficiency (Eg) is a probable sign of hard effort (Kong et al, 2015 ; Tamburro et al, 2020 ). In theory, Eg and Lp are highly anticorrelated, a reduction of Eg is equivalent to an increase of Lp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future efforts should look at neural correlates of CRF by studying brain activity and connectivity within the wide motor network regions, in particular the sensory and frontal cortical regions given their potential roles in supraspinal fatigue. To this end, advanced processing techniques, like independent component analysis or source imaging, have been successfully used to study fatigue in endurance cycling [ 62 ] and air traffic control [ 63 ]. In addition, corticomuscular coherence can study changes in brain to muscle drive or muscle to brain afferent inputs in CRF compared to healthy individuals [ 60 ].…”
Section: Discussionmentioning
confidence: 99%